1998
DOI: 10.1097/00005768-199805000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the Computer Science and Applications, Inc. accelerometer

Abstract: These data provide a template on which patterns of activity can be classified into intensity levels using the CSA accelerometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
2,943
12
75

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,304 publications
(3,068 citation statements)
references
References 8 publications
38
2,943
12
75
Order By: Relevance
“…Published cutpoints were used to examine the correlation between activity counts and self-report activity subdivided into low intensity and moderate-intensity activity and above. No women fell within the moderate-intensity activity category on any occasion using the cut points of X574 (Swartz et al, 2000) and X1952 (Freedson et al 1998). Only the lower cut point of X191 (Hendelman et al, 2000) identified individuals with activity of moderate intensity or above.…”
Section: Resultsmentioning
confidence: 99%
“…Published cutpoints were used to examine the correlation between activity counts and self-report activity subdivided into low intensity and moderate-intensity activity and above. No women fell within the moderate-intensity activity category on any occasion using the cut points of X574 (Swartz et al, 2000) and X1952 (Freedson et al 1998). Only the lower cut point of X191 (Hendelman et al, 2000) identified individuals with activity of moderate intensity or above.…”
Section: Resultsmentioning
confidence: 99%
“…(21, 48) The following cut-points and the corresponding thresholds were used: sedentary (0–100 counts/min), light (100–2199 counts/min), moderate (2200 – 5099 counts/min) and vigorous (>5100 counts/min). Missing values were estimated for children who had at least two days of eight hours of accelerometer wear time, using a sex-specific multiple imputation technique via PROC MI in SAS (Version 9.0, SAS Institute, Inc., Rockville, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were required to accumulate at least 10 h of physical activity per day, for a total of 4 days, to be eligible for further analysis. Physical activity of 100-1951 counts per minute (CPM) was classified as light, and ≥ 1952 CPM was classified as moderate to very vigorous, in accordance with previous studies [17,18]. Total counts from the three axes of the accelerometer were combined and divided by total wear time to generate a standardized measure of physical activity.…”
Section: Objective Measurement Of Physical Activitymentioning
confidence: 86%